4-Nitrobenzaldehyde removal by catalytic ozonation in the presence of CNT. (December 2020) - Santos, A. Sofia G.G.; Orge, Carla A.; Soares, O. Salomé G.P.; Pereira, M. Fernando R.
Graphical abstract: Highlights: Carbon nanotubes are used as catalyst for ozonation of 4-nitrobenzaldehyde. Physical/chemical modifications performed to enhance the catalytic activity. Single ozonation allows pollutant degradation, but not high mineralization. Catalyst addition improves mineralization, with good stability in cyclic runs. OH radicals play a key role in single ozonation, but not in catalytic ozonation. Abstract: 4-nitrobenzaldehyde (4-NBA) degradation pathway was studied during single and catalytic ozonation processes. Multi-walled carbon nanotubes (CNT) were used as ozonation catalysts and different textural and chemical modifications were performed to obtain samples with enhanced catalytic activity (CNT(BM) and CNT-M(BM 4 h)). Single ozonation was capable of total pollutant degradation after 180 min of reaction; however, complete mineralization was not achieved, reaching nearly 40 % of total organic carbon (TOC) removal. Catalytic ozonation presented a faster pollutant removal rate, and a high content of organic matter was removed in the first 30 min of reaction. For this specific case, the incorporation of nitrogen heteroatoms in the CNT structure (sample CNT-M(BM 4 h)) did not actively contribute to increasing the performance of the material, achieving a mineralization degree very similar to that obtained with the commercial catalyst (CNT) at the end of the reaction. The most promising catalyst was the ball-milled sample, CNT(BM), attaining 60 % of mineralization degree after 180 min of reaction. The catalyst CNT(BM) proved to be stable even after several reuses, presenting a loss of efficiency of 15 % in terms of TOC from the first to the fifth cycle. Radical scavenger experiments revealed that there is a significant contribution of OH radicals during single ozonation, whereas for catalytic ozonation process the reaction mechanism is quite different with less involvement of OH radicals in solution and a large contribution of the pathway involving adsorption and surface reactions.